The responsive web - Carver, Matthew (Manning Publications, 2015)
The Responsive Web builds on the best practices that have shaken out over a few years of production experience. This concise book skips pure theory and shows you exactly how to make responsive web design work for you in the real world. You'll learn innovative ways to use what you already know along with design techniques leveraging new HTML5 and CSS3 features. Along the way, you'll discover strategies to balance apps and websites, manage browser incompatibilities, and learn when multiple versions are the best option.